Adaptation of the Russian version of the ASAS health index - I. Z. Gaidukova; A. I. Akulova; A. P. Rebrov; A. G. Bochkova; S. Ya. Startsev; Sh. Erdes; E. K. Gaidukova; D. A. Poddubny (Научно-практическая ревматология)
ASAS health index (ASAS HI) is a comprehensive tool developed on the basis of the international system of ICF (the International Classification of Functioning, Disability and Health) to quantify the health of patients with spondyloarthritis (SPA), including ankylosing spondylitis (AS). ASAS HI is a questionnaire containing 17 questions, each related to a specific ICF pool (pain, emotions, sleep, sexual function, mobility, self-care and communication). ASAS HI additionally includes 9 questions (ASAS EF Item Set) to assess the impact of environmental factors on the health of the patient with SPA. The aim is a Russian translation and adaptation of the ASAS HI (including ASAS EF Item Set). Material and methods. Translation of ASAS HI and ASAS EF Item Set from English into Russian and its adaptation were carried out in five stages: the stage of direct translation; the stage of synthesis of translations and formation of the Russian version; the stage of reverse translation from Russian into English; the stage of comparison of the original English-language questionnaire with the result of reverse translation and the formation of the final Russian-language version; field test. Results and discussion. Three researchers performed an independent translation of ASAS HI (including ASAS EF Item Set), after which the fourth researcher created and agreed on a single Russian version of the questionnaire. Then two volunteers, for whom English is the main language, performed a reverse translation of ASAS HI from Russian into English (reverse translation). An independent researcher has compared the original and the resulting reverse translated English version of the ASAS HI, and then the three translators performed the joint correction of the text of the three questions, differing in English-language versions. The obtained second Russian-language version of ASAS HI (including ASAS EF Item Set) was tested by 10 patients with SPA: AS – 60%; non-radiological axial spondylitis (NR axSPA) – 40%, men – 60%; mean age – 32±12 years; duration of symptoms – 7.5±2.2 years; BASDAI index – 3.39±3.04; ASAS HI – 6,96±3,35.The average time to fill the questionnaire – 2,2±1,18 min. Patients rated the Russian version of the questionnaire as clear, easy to fill in and comprehensively characterizing health problems related to SPA. The results of testing Russian-speaking patients are comparable with the results obtained in testing 206 patients with SPA from 19 non-English-speaking and 4 English-speaking countries (AS – 65%; men – 59.7%; mean age – 42.4±13.9 years; duration of symptoms – 11.2±11.0 years; BASDAI – 3.8±2.3; ASAS HI – 7.1±4.4; filling time – 2.6±1.6 min). Conclusion. During the study translation and adaptation of the Russian version of ASAS HI, which is a tool for comprehensive assessment of health and function of patients with SPA, including AS were performed.